THE IMPACT WAQF LAND DEVELOPMENT IN PERLIS STATE - Mohamad Khadafi Hj Rofie; Zainal Md Zan; Nurul Hafizah Mohd Idrus (Journal of Islamic, Social, Economics and Development, 2018)
The development of waqf land is an initiative to enhance the dignity and majesty of Islam not only the aspects of faith but also the economy, education, society, politics and others. The study aims to assess the impact of waqf land development in the state of Perlis and the barriers that exist in the development of wakaf land in Perlis state. The method for obtaining data in this study is through interviews and observation methods in the field. The findings show that the development of waqf land in Perlis state has a good impact on respondents and stakeholders. The findings of the study show that the development of waqf land in Perlis state has an effect on moving economic, education and health activities to Perlis residents.